Kesan Tahap Realisme Agen Pedagogi Berbeza Terhadap Pencapaian Dan Motivasi Pelajar Dalam Pembelajaran Atas Talian - Sahimi, Saidatul Maizura (2010)
This study was conducted to elucidate the effects of different levels of realism of the pedagogical agent on student achievement and motivation in online learning. It involved three different levels of realism of the pedagogical agent, namely, the pedagogical agent with a cartoon character, the pedagogical agent with an illustrative character and the pedagogical agent with a realistic character. The Moodle open source Learning Management System was used as a delivery platform in the online learning and the pedagogical agents were embedded in it.